تركيب العطف في العربية-دراسة لسانية - حضري, عز الدين (University of El-oued, 2020)
يهدف هذا البحث إلى المساهمة في مواكبة النقاش الدائر حول البنية التركيبية للعطف وذلك بتحديد خصائص العاطف والمعطوفات في العربية. تكمن أهمية البحث في الوقوف على البنية التركيبية للعطف لتذليل الإشكالات التي يطرحها في اللغات عموما، مما يمكن من توفير رؤى مهمة حول هندسة العطف. يقوم الاستدلال التركيبي المعروض هنا على مجموعة من الافتراضات التي ما زالت محط نقاش أهمهما أن العطف لا يتوفر على إسقاط خاص به وأن رابط العطف لا يفحص الإعراب وبالتالي لا يتوفر على خصائص الرؤوس في اللغات الطبيعية. خلص البحث أن التناظر القائم بين المعطوفين يقدحه العاطف من خلال تفعيل عملية "انسخ" الشيء الذي يمنع افتراض إسقاط خاص بالعطف مما يمكن من دحض التحليل الجملي للعطف. لرصد تركيب العطف في العربية يتبنى البحث البرامج الأدنى إطارا نظريا للعمل. الكلمات المفتاح: عطف- تناظر- تطابق- إعراب- عطف جملي. Abstract This research aims to contribute to keeping debate about the syntactic structure of coordination, by identifying the characteristics of coordinators and conjuncts in Arabic.The importance of research appears in identifying the syntactic structure of coordination in order to reduce the problems it poses in languages in general, thus providing important insights about Some architectural issues in coordination.The reasoning presented here is based on a set of assumptions that are still under discussion, the most important of which is that coordination does not have its own projection and that the coordinators does not examine the case and therefore does not have the properties of the heads in natural languages.The research concluded that the symmetry that exists between the two conjuncts is motivated by coordinator by activating the process of "copy", which can refute the Clausal Conjunct Hypothesis .To deal with the syntax of coordination in Arabic, the research adopts the minimalist program as a theoretical framework for work. Keywords : coordination-symmetric- agreement- case- Clausal Conjunct
مقال. مجلة القارئ للدراسات الأدبية والنقدية. مج03. ع.01. جامعة الوادي
Keywords: عطف ; تناظر ; تطابق ; إعراب ; عطف جملي